Intersection Efficiency Improvement through Signal Optimization: A Case Study of Pushpalal Chowk (Mahendra Chowk), Butwal - Singh, Samridhi; Sapkota, Aayushma; Dhungel, Subhash (International Journal on Engineering Technology, 2025)
Traffic congestion has emerged as a major challenge in Butwal, Nepal, driven by rapid urbanization, population expansion, and a growing number of vehicles. Puspalal Chowk, a critical junction linking important routes such as Siddhartha Highway and the Butwal-Bhairahwa road, faces heavy traffic volumes, resulting in frequent congestion. This study aims to optimize the traffic signal system at Puspalal Chowk using SIDRA Intersection 8.0 software. Data was gathered over a 72-hour period, and the intersection's geometric features were manually documented. A model was created in SIDRA 8.0 to evaluate traffic conditions during peak hours (morning, afternoon, evening and night) following signal optimization. The findings reveal notable improvements, with reductions in average delays and queue lengths, especially during peak traffic times. The optimized signal timing plans enhanced the Level of Service (LOS) at the intersection, underscoring the effectiveness of signal optimization in improving traffic flow and alleviating congestion.